2018
DOI: 10.1007/s00246-018-1962-0
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Exercise Performance in Children and Adolescents with Repaired Tetralogy of Fallot Using Stress Echocardiography

Abstract: Exercise performance is variable and often impaired in patients with repaired tetralogy of Fallot (rTOF). We sought to identify factors associated with exercise performance by comparing high to low performers on cardiopulmonary exercise testing (CPET) in patients with rTOF. We conducted a cross-sectional study of subjects presenting for CPET who underwent echocardiograms at rest and peak exercise. Patients with pacemakers and arrhythmias were excluded. Right ventricular (RV) global longitudinal strain was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Of the 913 records initially identified, 56 23–78 studies with a total of 1730 patients were included in the qualitative synthesis (Figure 1). Of these 56 studies, 23 23–45 studied subpulmonary RV reserve in patients with repaired TOF, 19 46–64 assessed systemic RV reserve, and 14 65–78 assessed subpulmonary RV reserve with or without RV‐pulmonary arterial coupling in patients with PAH.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 913 records initially identified, 56 23–78 studies with a total of 1730 patients were included in the qualitative synthesis (Figure 1). Of these 56 studies, 23 23–45 studied subpulmonary RV reserve in patients with repaired TOF, 19 46–64 assessed systemic RV reserve, and 14 65–78 assessed subpulmonary RV reserve with or without RV‐pulmonary arterial coupling in patients with PAH.…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacologic stress with continuous infusion of incremental dose of dobutamine was employed in 22 studies 23–33,46–52,65–68 . On the other hand, exercise stress with either bicycle 34–45,53–64,69–76 or treadmill exercise testing 77,78 was used in 34 studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a few studies have suggested that physical or pharmacological stress may unmask abnormalities of right ventricular function in patients with repaired Tetralogy of Fallot, with normal right ventricular function under resting conditions [86,87]. SE allows the simultaneous assessment of right and left ventricular global and regional function and Doppler parameters as well as coronary flow reserve in posterior descending coronary artery and chronotropic reserve [88] can be impaired in these patients and are potential determinant of exercise capacity [89].…”
Section: Introductionmentioning
confidence: 99%